The effect of prior exercise intensity on oxygen uptake kinetics during high-intensity running exercise in trained subjects - do Nascimento P.C. (2015)
© 2014, Springer-Verlag Berlin Heidelberg.Purpose: The aim of this study was to compare the effects of two different kinds of prior exercise protocols [continuous exercise (CE) versus intermittent repeated sprint (IRS)] on oxygen uptake (VO2) kinetics parameters during high-intensity running. Methods: Thirteen male amateur futsal players (age 22.8 ± 6.1 years; mass 76.0 ± 10.2 kg; height 178.7 ± 6.6 cm; VO2max 58.1 ± 4.5 mL kg−1 min−1) performed a maximal incremental running test for the determination of the gas exchange threshold (GET) and maximal VO2 (VO2max). On two different days, the subjects completed a 6-min bout of high-intensity running (50 % ∆) on a treadmill that was 6-min after (1) an identical bout of high-intensity exercise (from control to CE), and (2) a protocol of IRS (6 × 40 m). Result: We found significant differences between CE and IRS for the blood lactate concentration ([La]; 6.1 versus 10.7 mmol L−1, respectively), VO2 baseline (0.74 versus 0.93 L min−1, respectively) and the heart rate (HR; 102 versus 124 bpm, respectively) before the onset of high-intensity exercise. However, both prior CE and prior IRS significantly increased the absolute primary VO2 amplitude (3.77 and 3.79 L min−1, respectively, versus control 3.54 L min−1), reduced the amplitude of the VO2 slow component (0.26 and 0.21 L min−1, respectively, versus control 0.50 L min−1), and decreased the mean response time (MRT; 28.9 and 28.0 s, respectively, versus control 36.9 s) during subsequent bouts. Conclusion: This study showed that different protocols and intensities of prior exercise trigger similar effects on VO2 kinetics during high-intensity running.